IMPROVING STUDENTS’ CONCENTRATION AND LEARNING OUTCOMES THROUGH PROJECT-BASED LEARNING ASSISTED BY GAMES AS THE METHOD - Vika Mutiara Ghozelin; Agnes Herlina Dwi Hadiyanti; Yohanes Bruri Kriswanto (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper addresses the issue of students’ low concentration and learning outcomes at SD Kanisius Demangan Baru 1. The purpose of the study is to improve students’ concentration and learning outcomes through a project-based learning model assisted by the game method. This research uses a classroom action research design. The research subjects were students of class 4A, and the research object was the improvement of students’ concentration and learning outcomes. Data were collected through observation, interviews, and tests, and analyzed using both quantitative and qualitative techniques.The results indicate that before the intervention, students’ concentration was low at 58.33%. After the first cycle, it increased to the moderate category at 69.44%, and after the second cycle, it reached the excellent category at 90.27%. Similarly, students’ learning outcomes improved from a low category average of 57.27 before the intervention to a medium category of 67.72 after the first cycle, and finally to a high category of 84.09 after the second cycle. These findings demonstrate that enhancing students’ concentration directly influences their learning outcomes, as focused attention allows students to optimize their ability to absorb and respond to the lessons learned.